Tuberculosis: expression of beauty, horror and pain (Colombia Medica, 2009)
Tuberculosis is one of the oldest illnesses in history, probably would be the first disease that affected human. Along the time it had been present in various civilizations making it´s legacy at different contexts. This article explores some pictorial perspectives inspired on that disease, ranging from beauty to horror and pain depending on the emotion that motivates the artist. It takes as references some artistic style and pictoric pieces to illustrate the different conceptions of the disease passing by the Renaissance, Baroque, expressionism and abstract movements